Butete the story of a remarkable fish - Gundaya, Asela Hazel Z. 1949- (Xlibris Corporation, 2009)
"This is a story of a puffer fish called butete. he has been discriminated in the fish world because of his appearance. He lived a peaceful life, until one day, he almost died on the shoreline. But neptune, the god of the sea, gave him another chance at life. Butete was able to live a happy and meaningful life. The story teaches us to respect one another and to acknowledge that each and every one of us is here for a reason."